THE IMPORTANCE OF MARKET THEORIES IN STOCK MARKET ANALYSIS - Alikulov Azamat , Tuygunovich (THE INNOVATION ECONOMY, 2025)
these scientific article is dedicated to the analysis of theories widely used by investors and issuers operating in the stock market for market analysis and assessment. Additionally, by identifying the advantages and disadvantages of several theories, a guide has been developed for the quality organization of the market evaluation and asset selection processes, which helps in making optimal decisions